Characterizing glare effects associated with diffractive optics in presbyopia-correcting intraocular lenses - Łabuz, Grzegorz; Khoramnia, Ramin; Yan, Weijia; van den Berg, Thomas J. T. P.; Auffarth, Gerd U.; Naujokaitis, Tadas; Tandogan, Tamer (Journal of cataract and refractive surgery, 2024)
Purpose: - To objectively quantify glare of intraocular lenses (IOLs) using a diffractive principle to extend the visual range and to identify models with increased susceptibility to inducing glare. - Setting: - David J Apple Laboratory, Heidelberg, Germany. - Design: - Laboratory investigation. - Methods: - Glare was assessed by means of a straylight parameter with a standard C-Quant intended for 7 degrees. In addition, 2 C-Quant modifications were used to test lower angles (ie, 2.5 degrees and 3.5 degrees). The following IOL models were assessed: PanOptix, AT Lisa Tri, Synergy, and Triumf, the latter 2 with chromatic aberration correction at distance. Straylight from trifocal IOLs was compared against a monofocal W-60R lens. The C-Quant test was performed through the studied IOLs by using additional optical components attached to their ocular. - Results: - Straylight (deg2sr−1) of the control was <1 at all tested angles, with the trifocal models showing comparable straylight at 7 degrees. At 3.5 degrees, Triumf's straylight increased to 15.5 ± 0.6, followed by Synergy (6.2 ± 1.1), PanOptix (4.1 ± 0.3), and AT Lisa Tri (2.0 ± 0.8). The chromatic aberration-correcting models demonstrated correspondingly higher straylight (Synergy: 18.8 ± 1.3; Triumf: 17.3 ± 0.5) at 2.5 degrees compared with PanOptix (4.3 ± 0.4), AT Lisa Tri (2.1 ± 0.1), and monofocal IOLs yielding minimal or no increase. - Conclusions: - Trifocal IOLs induced increased straylight, but it was limited to lower angles, which may cause difficulties detecting these effects using a standard clinical approach. The latest IOL designs featuring chromatic aberration correction at far focus seem more susceptible than the established trifocal IOLs to inducing a glare phenomenon.
Gesehen am 24.02.2025